AKTIVISME DIGITAL DAN GERAKAN MENUJU PERUBAHAN SOSIAL: TINJAUAN LITERATUR SISTEMATIS GERAKAN MEDIA SOSIAL - Rahayuningsih, Nur Octavia Dian; Aziz, Syamsuddin; Akbar , Muhammad (LPPM Stikosa - AWS, 2025)
This systematic literature review explores the role of social media in digital activism and its significance in mobilizing and raising awareness of social and political issues. By analyzing 26 relevant studies published between 2020 and 2024, this review highlights how social media platforms empower individuals and groups particularly youth to disseminate information, build collective awareness, and engage in public discourse. The findings indicate that digital activism has transformative potential in democratizing communication and amplifying marginalized voices. However, several challenges remain, such as the spread of misinformation, the hijacking of activism for conspiratorial agendas, and the difficulty in measuring the tangible impact of online actions on real-world social and policy change. The study also identifies the most frequently used theories (e.g., Social Movement Theory, Framing Theory, Connective Action), common research methods (qualitative, quantitative, and mixed methods), and thematic contexts such as racial justice, feminism, environmental activism, and misinformation. Most studies rely heavily on Twitter (X) as the primary platform, suggesting a need for cross-platform analysis in future research. This review concludes that while social media is an essential tool for digital activism, further research is required to develop effective communication strategies, assess long-term impacts, and explore activism in the Global South. Ultimately, this study contributes to the growing body of knowledge on media and communication by emphasizing the complex, dynamic, and evolving nature of digital activism in shaping sustainable social change.